Concomitant Immunity and Worm Senescence May Drive Schistosomiasis Epidemiological Patterns: An Eco-Evolutionary Perspective - Buck, Julia C.; De Leo, Giulio A.; Sokolow, Susanne H. (Frontiers in Immunology, 2020)
In areas where human schistosomiasis is endemic, infection prevalence and egg output are known to rise rapidly through childhood, reach a peak at 8-15 years of age, and decline thereafter. A similar peak (“overshoot”) followed by return to equilibrium infection levels sometimes occurs a year or less after mass drug administration. These patterns are usually assumed to be due to acquired immunity, which is induced by exposure, directed by the host’s immune system, and develops slowly over the lifetime of the host. Other explanations that have been advanced previously include differential exposure of hosts, differential mortality of hosts, and progressive pathology. Here we review these explanations and offer a novel (but not mutually exclusive) explanation, namely that adult worms protect the host against larval stages for their own benefit (“concomitant immunity”) and that worm fecundity declines with worm age (“reproductive senescence”). This explanation approaches schistosomiasis from an eco-evolutionary perspective, as concomitant immunity maximizes the fitness of adult worms by reducing intraspecific competition within the host. If correct, our hypothesis could have profound implications for treatment and control of human schistosomiasis. Specifically, if immunity is worm-directed, then treatment of long-standing infections comprised of old senescent worms could enable infection with new, highly fecund worms. Furthermore, our hypothesis suggests revisiting research on therapeutics that mimic the concomitant immunity-modulating activity of adult worms, while minimizing pathological consequences of their eggs. We emphasize the value of an eco-evolutionary perspective on host-parasite interactions.